Professional development of teachers in conditions digitalization of education - Stukalenko, Nina; Imanova, Aliya; Mukanova, Roza (Pedagogy and Psychology, 2021)
The article discusses the development of digital technologies in education. Digitalization in education is a new paradigm that provides for new opportunities and new forms of communication and interaction of educational subjects; effective means of obtaining quality education. Individualization of vocational education and training based on digital technologies allows for an organic transition to multiprofessionalism - a post-industrial model of professionalism, when the profession ceases to be a standardized set of labor functions and actions, demanded knowledge, skills and abilities - and becomes a dynamic personalized set of competencies. Digitalization is one of the ways to make education of the same quality for everyone. With “digital” it is easier and faster to form a personalized approach to students, it is easier to implement differentiated teaching that takes into account the needs of each student.